2013
DOI: 10.1016/j.biomaterials.2013.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of keratocyte phenotype by collagen fibril nanoarchitecture in membranes for corneal repair

Abstract: Type I collagen membranes with tailored fibril nanoarchitectures were fabricated through a vitrification processing, which mimicked, to a degree, the collagen maturation process of corneal stromal extracellular matrix in vivo. Vitrification was performed at a controlled temperature of either 5 °C or 39 °C at a constant relative humidity of 40% for various time periods from 0.5 wk up to 8 wk. During vitrification, the vitrified collagen membranes (collagen vitrigels, CVs) exhibited a rapid growth in fibrillar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…However, certain types of cellular protrusions have also been observed to oscillate with a constant period on the order of tens of seconds47, which suggests that the dynamics of local stiffness are a promising direction for future study. Furthermore, while we have only considered isotropic networks, tissues can have aligned fibres due to remodelling and prestrain1348. Our results for isotropic prestrain suggest that aligned networks should yield a narrower stiffness distribution when probed along a fixed direction.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, certain types of cellular protrusions have also been observed to oscillate with a constant period on the order of tens of seconds47, which suggests that the dynamics of local stiffness are a promising direction for future study. Furthermore, while we have only considered isotropic networks, tissues can have aligned fibres due to remodelling and prestrain1348. Our results for isotropic prestrain suggest that aligned networks should yield a narrower stiffness distribution when probed along a fixed direction.…”
Section: Discussionmentioning
confidence: 88%
“…Eukaryotic cells, including fibroblasts, mesenchymal stem cells and cancer cells, attach to substrates via transmembrane protein complexes called focal adhesions, allowing the cell to sense stiffness3891011. Knockdown studies have established that this mechanosensing contributes both to motility and to the regulation of cell shape in three-dimensional in vitro systems that closely resemble in vivo cellular environments11121314151617, where cells are surrounded by a loosely connected, disordered network of protein fibres, such as collagen or fibrin18. These biopolymers form a major structural component of the extracellular matrix (ECM), which serves as the physical scaffolding within which cells live and move.…”
mentioning
confidence: 99%
“…By exerting tangential stretching forces on the collagen, the fibroblasts under the physiological conditions of the tissues can organize the collagen fibrils into sheets and cables, which in turn drastically changes the alignment of the collagen-fiber network (1). This dynamic change in the alignment of collagen fibers by the fibroblasts results in reciprocal changes through feed-forward signaling that further dictates the orientation, morphology, and alignment of neighboring cells (e.g., keratinocytes and epithelial cells) (15). Collagen molecules and fibers typically bind to other components of the ECM, such as elastins, whose fibers provide the elastic and recoil properties of tissues that undergo repetitive stretching.…”
Section: Mechanics and The Ecmmentioning
confidence: 99%
“…On a cellular level, mechanical properties by crosslinking cause an increase in density of collagen fibers in the material. It has been previously shown that collagen fiber density correlates with proliferation and morphology of keratocytes . Optical properties do not directly relate to keratocyte function or proliferation but are critical for maintaining vision after application.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously noted that collagen substrates readily support cellular proliferation . Thus, this collagen scaffold would initially serve to hold corneal cells and would be remodeled over time to more organized structures.…”
Section: Introductionmentioning
confidence: 99%